The tennis court oath : a book of poems - Ashbery, John, 1927-2017 (Wesleyan poetry classics., 1962)
Still a touchstone of contemporary avant-garde poetry today, this 35th anniversary edition of John Ashbery's second book celebrates an American poet who has won a Pulitzer Prize, a National Book Award, and a National Book Critics Circle Award.